Multiple solutions for an anisotropic elliptic equation of Kirchhoff type in bounded domain - Nguyen Thanh Chung (Results in Nonlinear Analysis, 2018)
In this paper, we consider a class of anisotropic elliptic equations of Kirchhoff type